Impact of Rhythmic Patterns in Odissi Music on Sleep and Relaxation - Pani , Aurosish; Pratibha Sharma (International Journal of Computational and Experimental Science and Engineering, 2025)
Music and dance have always been known for their therapeutic, health-related, and spiritual benefits for human beings. There are countless studies that discuss how people have experienced deep spiritual feelings just by listening to quality music. Along with this, many other factors are being explored to understand how music can affect the mental and physical well-being of individuals. This study focuses specifically on sleep-related and relaxation-related aspects. The data has been collected using AI-powered healthcare gadgets, including advanced wearable devices.This is an experimental study conducted on 30 people who were exposed to different rhythmic patterns in Odissi music, and 30 people who were not exposed to any such music. The study was done in a closed environment to observe and compare the sleep and relaxation patterns between the two groups—listeners and non-listeners.Although the main focus is on how Odissi music affects sleep and relaxation, very little research exists on how rhythmic patterns in this music influence these factors. In reality, studying the impact of rhythmic patterns at a deep level is highly technical and requires specialized instruments. So, the study relied on participants’ responses about the nature of the music they listened to. Most of them listened to music with different rhythmic patterns, and the aim was to find a relationship between these patterns and their levels of relaxation and sleep quality. The study included 30 participants aged between 24 and 35 who listened to Odissi music and another set of 30 participants of the same age group who did not. The goal was to create two observation groups and see how their exposure or non-exposure to Odissi music affected their ability to relax and sleep. Participants were chosen from similar backgrounds (demographic and psychographic) to reduce the influence of any extra variables and to make the comparison valid.The study concludes that Odissi music, especially its rhythmic structure, has the potential to act as a natural aid for relaxation and better sleep. Future research with a larger sample size and brainwave tracking can provide deeper insights.